Fibrous scaffolds fabricated by emulsion electrospinning: from hosting capacity to in vivo biocompatibility - Spano, F; Quarta, A; Martelli, C; Ottobrini, L; Rossi, R M; Gigli, G; Blasi, L (Nanoscale, 2016)
Electrospinning is a versatile method for preparing functional three-dimensional scaffolds. Synthetic and natural polymers have been used to produce micro- and nanofibers that mimic extracellular matrices. Here, we describe the use of emulsion electrospinning to prepare blended fibers capable of hosting aqueous species and releasing them in solution. The existence of an aqueous and a non-aqueous phase allows water-soluble molecules to be introduced without altering the structure and the degradation of the fibers, and means that their release properties under physiological conditions can be controlled. To demonstrate the loading capability and flexibility of the blend, various species were introduced, from magnetic nanoparticles and quantum rods to biological molecules. Cellular studies showed the spontaneous adhesion and alignment of cells along the fibers. Finally, in vivo experiments demonstrated the high biocompatibility and safety of the scaffolds up to 21 days post-implantation.